Cost-Effectiveness Analysis of ERACS Compared to Non-ERACS at Hospital - Basleman, Balqis Hisyam Saleh; Susiyadi, Susiyadi; Setiawan, Didik (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Cesarean section has a 5 to 7 times greater risk of maternal and child mortality than prevaginal delivery. Several other complications, namely reduced mobility, prolonged pain in the surgical wound, and longer hospital stays affect the patient's quality of life. The ERACS protocol, which is a multidisciplinary approach, is a good strategy to reduce the negative effects of cesarean section.Objectives: To find out whether the ERACS protocol is more cost-effective than the non-ERACS protocol from a patient’s perspective.Methods: Researchers took data on costs and quality of life (using EQ-5D-5L) prospectively at private hospitals in Wonosobo which then calculated the value of the ICER. The cost components measured include direct medical and non-medical costs as well as indirect costs. The effectiveness of the measures in this study was reported in terms of reducing the LOS to 1 day, which represents a faster recovery and reduced costs. In this study, there were 2 sample groups, namely the ERACS protocol group with 24 respondents and the non-ERACS protocol group with 75 respondents.Results: Based on the research, the effectiveness of the protocol in the form of improving the quality of life of patients was seen from the utility value and higher costs in the ERACS group compared to the non-ERCAS group (utility 0.771 vs 0.715; cost IDR.16,127,183 ± 5,023,356 vs IDR. 10,459,562 ± 3,826 .424) and obtained an ICER of 94,311,767 which means that the patient needs to add IDR.94,311,767 to improve the quality of life of post-cesarean section patients, which value is higher than Indonesia's 2022 GDP.Conclusion: ERACS measures are more cost-effective when compared to non-ERACS measures because the ICER value is below three times Indonesia's 2022 GDP according to the perspective of patients at private hospitals in Wonosobo.